Kinetic study of Fenton-like degradation of Methylene blue in Aqueous solution using calcium peroxide - Li, Fan; Shean, Thomas Yaw Choong; Soltani, Soroush; Abdullah, Luqman Chuah; Md. Jamil, Siti Nurul Ain (Universiti Putra Malaysia Press, 2022)
The textile industry is one of the fastest-growing industries that significantly contribute to the economic growth in Malaysia. Dyeing wastewater is one of the more difficult to control in industrial wastewater. Methylene blue is a widely used dye in the textile industry, which cannot be discharged directly into the natural environment without treatment. The present study involves the degradation of methylene blue by a Fenton-like system using calcium peroxide (CaO2, CP). The process of degradation was recorded spectrophotometrically. The field emission scanning electron microscope (FESEM) and energy dispersive X-ray (EDX) were measured for testing the purchased commercial calcium peroxide. The effect of pH, the initial dosage of CaO2, and temperatures were studied with kinetics modeling, respectively. The results indicated that 97.07% removal of methylene blue took place at the optimum condition (pH=3.0, initial CaO2 dosage=3.0 g, 65°C, 150 rpm, contact time=60 minutes). Over four models (zero-order, first-order, second-order, Behnajady, Modirshahla, and Ghanbary (BMG) model) applied in this study, the BMG model with the R2 =0.9935 was in accordance with the experimental data.